Diminished ovarian reserve in patients with psoriasis - Burcu Tuğrul Ayanoğlu; Elif Didem Özdemir; Onur Türkoğlu; Aslıhan Alhan (Elsevier, 2018)
Objective: Psoriasis is a multi-systemic chronic inflammatory skin disease. Previous data suggests that women with some chronic inflammatory diseases have diminished ovarian reserve. This study explores ovarian reserve in patients with psoriasis. Materials and methods: We prospectively analyzed 14 female patients with psoriasis and 35 healthy age and body mass index matched controls. An interview explored demographic characteristics, obstetrical history and menstrual characteristics. Psoriatic area severity index (PASI) in patients was assessed. Estrogen, follicle-stimulating hormone (FSH), luteinizing hormone (LH), thyroid stimulating hormone and with gynecologic ultrasonography, ovarian volume and antral follicular count (AFC) were measured in both study and control groups. These values were analyzed with changes of the PASI in the patient group. Results: Patients with psoriasis had significantly higher levels of FSH and FSH/LH ratio than healthy controls (p = 0.039, p = 0.005 respectively). AFC of psoriasis patients were significantly lower than healthy controls (p = 0.002).There were no significant difference among other hormone levels and ovarian volumes (p > 0.05). The hormone levels, ovarian volume and AFC were not correlated with PASI of the patients. Conclusion: The results of the study suggest that patients with psoriasis may have diminished ovarian reserve. Keywords: Psoriasis, Ovarian reserve, Psoriatic area severity index, Antral follicular count, Follicle-stimulating hormone